Influence of milling whole wheat grains and particle size on thermo-mechanical properties of flour using Mixolab - Joseane Bressiani; Tatiana Oro; Paola Maria Lopes Da Silva; Flávio Martins Montenegro; Telma Elita Bertolin; Luiz Carlos Gutkoski; Marcia Arocha Gularte (Czech Journal of Food Sciences, 2019)
Whole grain wheat flour (WG) of three different particles sizes (194.9, 609.4, and 830.0 µm) was prepared by milling whole grain. The effect of particle size on the thermo-mechanical properties of flour was investigated using Mixolab equipment and solvent retention capacity (SRC). The results showed that particle size influences the functionality of the gluten network. The SRC test revealed that the water absorption increased from 77.43% to 85.76%, with decrease in particle size. The C2 (protein weakening) values were correlated with the values for water absorption in the SRC and wet gluten test, respectively. The degree of gelatinization of starch (C3) showed that the presence of the fibers in the WG samples limited the availability of water to the starch, and this effect was especially true for flour with smaller particle size. In summary, the Mixolab equipment allowed a better understanding of the functionality of WG with regard to the behavior of protein properties. WG with coarse particles demonstrated a greater impact on the gluten network, indicating a negative effect on the baking quality.